EXPLORING THE TEMOKAN TRADITION IN JAVANESE WEDDINGS: AN ANTHROPOLINGUISTIC APPROACH - Ramadhayani, Nanda; Perangin-angin, Alemina br; Mulyani, Rozanna (Universitas Islam Sumatera Utara (UISU), 2024)
This study explores the textual, contextual, and non-contextual elements of the Temokan tradition, a vital aspect of Javanese traditional wedding ceremonies. Specifically, it examines the interplay between text, co-text, and context within these ceremonial performances. Data were collected through interviews with informants and analyzed using a descriptive qualitative method combined with an ethnographic approach. The research identifies 10 distinct performances and 10 associated texts, involving 8 types of objects classified based on their co-textual features. The co-text in the Temokan tradition includes material elements such as objects used in the ceremonies, the spatial arrangement and distance between participants, and gestures that convey symbolic meaning. Contextual elements encompass ideological, social, cultural, and situational factors, illustrating the depth and richness of the tradition. These elements are further embedded with values and norms, including religious, logical, ethical, and aesthetic dimensions. Norms such as etiquette, customary practices, legal expectations, and habitual behaviors further reflect the tradition's cultural significance. From an anthropolinguistic perspective, the study highlights key performances such as Gantalan Sadak, Wiji Dadi, Wiji Suku, Sindur Binayang, Pangkon Timbang, Tanduring Pengantin, Kacar-Kucur, Dahar Kembul, Martuwi, and Sungkeman. These performances encapsulate the symbolic, cultural, and social meanings that sustain the Temokan tradition's role in preserving Javanese identity and heritage. This research contributes to understanding how linguistic and cultural practices interweave in traditional ceremonies.